Association between community violence exposure and teen parental firearm ownership: data from a nationally representative study - Karissa R. Pelletier; Jesenia M. Pizarro; Regina Royan; Rebeccah Sokol; Rebecca M. Cunningham; Marc A. Zimmerman; Patrick M. Carter (BMC, 2024)
Abstract Background Firearm injuries are the leading cause of death for U.S. adolescents. Given the prevalence of firearm ownership in the U.S., particularly among parental figures in homes with children and teens, and the relationship between firearm access and injury outcomes, it is vital to shed light on potential parental motivations for keeping firearms in their homes. The purpose of this analysis was to examine whether exposure to community violence is associated with parental firearm ownership. Methods Data from the Firearm Safety Among Children and Teens Consortium's National Survey (6/24/2020-7/24/2020) was examined. The survey sample comprised parents/caregivers of high-school-age teens (age 14-18). The survey examined various measures, including firearm ownership, storage, community violence exposure, and sociodemographic characteristics. Stepwise logistic regression was used to examine the association between community violence exposure and parental firearm ownership. Results The study included 2,924 participants, with 45.1% identifying as male, 12.9% identifying as Hispanic, and 25.3% identifying as non-White. Among these participants, 43.1% reported firearm ownership, and 49.9% reported exposure to community violence. Regression models demonstrate that community violence exposure is associated with an increased likelihood of firearm ownership among parents/caregivers of high-school age teens (OR = 1.08, p < 0.05). Other significant predictors of firearm ownership among parents/caregivers included parent/caregiver age (OR = 0.99, p < 0.01), marital status (OR = 1.29, p < 0.05), and educational attainment (OR = 0.60, p < 0.001). Conclusions The findings supported the hypothesis that community violence exposure was associated with an increased likelihood of parental firearm ownership, even after adjusting for potential confounders. These findings contribute to the existing literature by shedding light on the possible contributing factors for firearm ownership among parents/caregivers of teens. Public health interventions focused on raising awareness about the risks of firearm access in households with youths, providing counseling on locked storage practices, and offering resources for accessing secure firearm storage options, such as rapid access storage, may contribute to reducing firearm access among youth. Additionally, community-based initiatives focused on violence prevention and addressing the root causes of community violence can help create safer environments, thereby reducing the perceived need for accessible firearms in the home by parents and caregivers.